2005
DOI: 10.1128/aem.71.12.7788-7791.2005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Similarity of Flag Shoot and Ascospore Subpopulations of Erysiphe necator in Italy

Abstract: The overwintering mode of the grape powdery mildew fungus, Erysiphe necator (syn. Uncinula necator), as mycelium in dormant buds (resulting in symptoms known as flag shoots) or as ascospores in cleistothecia, affects the temporal dynamics of epidemics early in the growing season. We tested whether distinct genetic groups (I and III) identified previously in E. necator correlate to overwintering modes in two vineyards in Tuscany, Italy, to determine whether diagnostic genetic markers could be used to predict ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 14 publications
3
29
1
Order By: Relevance
“…The temporal isolation of genetic groups shown in our study thus prevents recombination between group A and B isolates, accounting for the maintenance of the highly differentiated genetic structures in E. necator populations, despite demonstrations of interfertility between these groups in controlled crossing experiments (26,37). Group B isolates may overwinter either within buds (8,29,32,41) or within cleistothecia formed by sexual reproduction, whereas group A isolates probably survive the winter exclusively within buds, which become infected at the beginning of the growing season (30). From an evolutionary point of view, this difference in survival strategy between the two genetic groups should confer an advantage on group B isolates, as these isolates benefit from both clonal and sexual reproduction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The temporal isolation of genetic groups shown in our study thus prevents recombination between group A and B isolates, accounting for the maintenance of the highly differentiated genetic structures in E. necator populations, despite demonstrations of interfertility between these groups in controlled crossing experiments (26,37). Group B isolates may overwinter either within buds (8,29,32,41) or within cleistothecia formed by sexual reproduction, whereas group A isolates probably survive the winter exclusively within buds, which become infected at the beginning of the growing season (30). From an evolutionary point of view, this difference in survival strategy between the two genetic groups should confer an advantage on group B isolates, as these isolates benefit from both clonal and sexual reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…An association between flag shoot symptoms and infection with group A isolates has also been reported in other studies (1,10,26). However, the association between the genetic group and the overwintering strategy has been challenged by the findings in recent studies reporting that flag shoot symptoms may be caused by both groups (8,28,29,32,41).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to this association, these authors proposed that group A isolates may be responsible for early infections in the season while group B isolates may be responsible for late infections (Délye and Corio-Costet 1998;Miazzi et al 2003). However, the association between genetic groups and over-wintering survival has been challenged by recent studies reporting that flag-shoot symptoms may harbour both group A and B isolates (Cortesi et al 2005;Nuñez et al 2006;Péros et al 2005;Willocquet et al 2007). Moreover, the hypothesis of a temporal succession of genetic groups was based on genetic studies that suffered from sampling strategies confounding time during the epidemic with over-wintering mode and source of inoculum.…”
Section: Introductionmentioning
confidence: 99%
“…Data available showed that the frequencies of the groups could vary greatly from one field to another, suggesting a high level of spatial heterogeneity at the vineyard scale (Cortesi et al 2005;Amrani and Corio-Costet 2006;Bouscaut and Corio-Costet 2007;Willocquet et al 2007).…”
Section: Introductionmentioning
confidence: 99%